Life cycle of oil palm bunch moth, Tirathaba mundella walker (Lepidoptera: Pyralidae) reared under laboratory conditions on artificial diet - Su, Chong Ming; King, Patricia Jie Hung; Tan, Calvin Zhe Khai; Kwan, Yee Ming; Ab Aziz, Zakri Fitri; Bong, Joseph Choon Fah; Ong, Kian Huat (Academic Publications, 2019)
Tirathaba mundella Walker is an important pest in many oil palm plantations especially those established on peatland. The life cycle of T. mundella has not been described in detail despite its economic importance. This study aimed to describe the bionomic characteristics of T. mundella, rearing on an artificial diet, at 25 oC. The duration of a complete metamorphosis cycle of T. mundella was about 51.63 ± 3.80 days. The incubation period was the shortest (3.33 ± 0.80 days.), The most detrimental stage of the pest to oil palm is at larval stage, which took 33.90 ± 2.60 days before pupating. The pupal period took about 5 to 11 days with a mean ± SD period of 8.53 ± 1.48 days. The average of the adult’s longevity was about 6.05 ± 1.81 days. There is no statistical difference between the duration of male and female longevity. Adult male and female moths reared in captivity feeded with 10% sucrose solution would mate readily and produce fertile eggs. The mean preoviposition period were 4 days. Successful of rearing T. mundella using artificial diet under laboratory conditions promises laboratory assessment for pesticide development which is less tedious and time consuming than conventional field experiments.